Expression of Fcγ receptors type II (FcγRII) in chronic lymphocytic leukemia B cells [4] - Gamberale, Romina (2003)
We have read with interest the paper from Damle et al analyzing the surface membrane phenotype of B lymphocytes in chronic lymphocytic leukemia (B-CLL). The authors stated that the leukemic cells from all B-CLL patients evaluated (irrespective of immunoglobulin heavy chain (IgVH) gene mutational status) bear the phenotype of antigen-experienced B cells based, among other features, on the very low expression of Fcγ receptors type IIb (FcγRIIb, CD32), which is the main isoform of FcγRII in B lymphocytes.